Downregulated microRNA-129-5p by Long Non-coding RNA NEAT1 Upregulates PEG3 Expression to Aggravate Non-alcoholic Steatohepatitis - Zhang, Zhi; Wen, Huiqing; Peng, Bangjian; Weng, Jun; Zeng, Fanhong (Frontiers in Genetics, 2021)
Long noncoding RNAs (lncRNAs) have recently emerged as inflammation-associated biological molecules with a specific role in the progression of liver fibrosis conditions including nonalcoholic steatohepatitis (NASH). The aim of this study was to elucidate the effects of lncRNA nuclear enriched abundant transcript 1 (NEAT1), microRNA-129-5p (miR-129-5p), and paternally-expressed gene 3 (PEG3) on the biological activities of hepatic stellate cells (HSCs) subjected to NASH. First, microarray-based analysis revealed up-regulated PEG3 in NASH. Liver tissues from mice fed a methionine-choline-deficient (MCD) diet exhibited increased expression of NEAT1 and PEG3 along with lower miR-129-5p expression. A series of in vitro and in vivo assays were then performed on HSCs after transfection with shPEG3, miR-129-5p mimic, or treatment with pyrrolidine dithiocarbamate (PDTC), an inhibitor of the NF-κB signaling pathway. Results confirmed the alleviated fibrosis by restoring miR-129-5p, while depleting PEG3 or NEAT1, as evidenced by the inactivation of HSCs. To sum up, NEAT1 can bind specifically to miR-129-5p and consequently regulate miR-129-5p and PEG3 expression in relation to the HSC activation occurring in NASH. Thus, NEAT1 targeted-inhibition against miR-129-5p presents a promising therapeutic strategy for the treatment of NASH.